STUDI KEANEKARAGAMAN ECHINODERMATA DI PESISIR PANTAI NGRUMPUT GUNUNG KIDUL - Awalia, Adhisty Putri; Permadani, Karunia Galih; Prajoko, Setiyo (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Indonesian waters have a high diversity and abundance of marine biota, one of which is Echinodermata species. This study aims to determine the diversity of Echinodermata species found on the coast of Ngrumput Beach, Gunung Kidul. This research is a type of exploratory descriptive research that uses the quadrat transect method when collecting data or Echinodermata samples. Meanwhile, data analysis in this study used the diversity index with the Shannon-Wienner formula and the relative abundance index using the van Balen formula. The results of this study indicate that there are 12 species of Echinodermata from 5 families and 3 classes, including Class Ophiuroidea, Class Echinoidea, and Class Holothuroidea. The most common species found at Ngrumput Beach is Echinometra oblonga, while Heterocentrotus trigonarius is the least common Echinodermata species found at Ngrumput Beach. The results of the calculation of the relative abundance index of Echinometra oblonga species are Di = 21% with a high category, while the results of the calculation of the relative abundance index in Heterocentrotus trigonarius species amounted to Di = 1% which is categorized as low.